(untitled) (Research Nepal Journal of Development Studies, 2025)
This research critically examines the multi-dimensionality of development by contrasting economic and non-economic indicators between countries at various stages of development, with a specific focus on Nepal. GDP and GNI per capita have traditionally been used as principal indicators of development. This research argues that these economic indicators on their own are insufficient to capture the nuances of human well-being. Drawing on non-conventional approaches such as Amartya Sen’s Capability Approach and holistic models of development, the study explores the variables through which education, health, governance, and life expectancy contribute to human development outcomes. Utilizing cross-country data, the study contrasts the high-income countries (United States, United Kingdom, France), developing nations (China, Brazil, Saudi Arabia), and least developed nations (Ethiopia, Chad, Nepal), employing a combination of descriptive statistics, correlation analysis, and linear regression. The findings show that, similar to poorer nations, economic growth is strongly correlated with human development in poorer nations but decreases in wealthier nations where the quality of institutions, social policies, and issues of equity matter more. Regression analysis reveals that GNI per capita explains approximately 80.2% of the HDI variation, establishing its relevance but also the remaining 20% of explained variation through variables other than economics. With a Nepal focus, the study shows that health and education gains can produce high development payoffs even with limited economic resources. The conclusion is that holistic approach merging economic performance with social, environmental and institutional variables, is crucial to achieving inclusive and sustainable development. The results have important implications for policymakers, particularly for developing and least developed nations, to invest more in human capital and institutional strengthening in addition to economic growth.